A detailed kinetic and mechanistic study of the regioselective hydrogenation of quinoline to 1, 2, 3, 4 tetrahydroquinoline catalyzed by [Os(H) (Cl) (CO) (PPh3)3] - Rosales, Merlín; Arteaga, María Andreina; González, Angel; González, Beatriz; Molina, Karely; Pérez, Homero; Vallejo, Regina (Ciencia, 1970)
Véase archivo PDF